紫杉醇联合卡铂三周方案同步胸部放疗治疗不宜手术的局部晚期非小细胞肺癌疗效和安全性研究：一项来自单中心的回顾性研究 (Zhongguo Fei Ai Za Zhi, 2016)
BACKGROUND AND OBJECTIVE: Standard care for patients with inoperable advanced non-small cell lung cancer (NSCLC) is concurrent chemoradiotherapy. The ideal concurrent chemotherapy regimen has not been determined. The aim of this study is to retrospectively analyze the efficacy and safety of concurrent radiotherapy with carboplatin/paclitaxel administrated every three weeks (PC three-week regimen) in inoperable advanced NSCLC and compare them with the results of cisplatin/etoposide. METHODS: The 43 patients with inoperable advanced NSCLC receiving concurrent chemotherapy in Peking Union Medical College Hospital from January 2012 to June 2014 were enrolled and analyzed. Of them, 15 patients received carboplatin/paclitaxel with concurrent thoracic radiotherapy; the other 28 patients received cisplatin/etoposide. Clinical characteristic, efficacy and toxicity data were compared in these two groups. RESULTS: For the overall population, the objective response rate (ORR) and disease control rate (DCR) were 41.9% and 90.7% respectively. The median progression free survival (PFS) was 10.6 months (95%CI: 7.4-13.8). And the median overall survival (OS) was 19.2 months (95%CI: 15.3-23.1). There were no significant differences in response rates (ORR: 33.3% vs 46.4%; DCR: 86.7% vs 92.9%, P=0.638), PFS (6.6 months vs 12.2 months, P=0.389), or OS (16.1 months vs 22.1 months, P=0.555) in either group. The adverse events were generally manageable and no treatment-related deaths occurred. CONCLUSION: Compared with PE, PC three-week regimen concurrent thoracic radiotherapy for inoperable advanced NSCLC has the similar efficacy and acceptable toxicity profile, which can be used in clinical setting.